Organizational resilience: What public managers do to ensure continued goal attainment during drastic changes - Lund, Clara Siboni; Hvilsted, Line; Salomonsen, Heidi Houlberg; Andersen, Lotte Bøgh (Politica, 2021)
Public organizations must keep attaining their goals during changes, and the concept of organizational resilience describes this ability. The article examines public managers’ leadership behaviors focused on promoting organizational resilience during drastic changes. Based on 24 interviews with public managers and professionals who worked with public health and elderly care during the Covid-19 pandemic, we shed light on four leadership behaviors aimed at ensuring organizational resilience: setting direction, supporting relations, facilitating reflections, and clarifying the rules of the game. We find that public managers particularly set direction by balancing opposing considerations in the daily work, and that their support of relations includes both employees and citizens. The managers facilitate opportunities to reflect differently with variation in whether they initiate and/or participate in the reflection process themselves. The rules of the game are changed toward either leader-centrism or self-governance (away from decision-making with both leader and employee participation). The four types of leadership behaviors are interrelated and interact with established types of leadership behaviors.